Pemaknaan Belajar Anak Non Disabilitas Bersama Teman Penyandang Disabilitas di Kelas Inklusif di Tk Sukma Nusa Bangsa - Lala Anoez; Nur Rahmiyati Luawo; Sofia K. Djafar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to reveal how non-disabled children interpret their learning experiences with friends with disabilities in inclusive classes. Inclusive classes are educational environments that combine non-disabled and disabled students in the same learning space, with the hope of creating equal and respectful interactions. The method used in this study is a qualitative approach with observation and data collection techniques. The results of the study show that non-disabled children interpret their learning experiences not only as an academic process, but also as a social and emotional learning process. They learn about empathy, tolerance, and cooperation, and show changes in attitudes towards diversity.